Quality assessment of brownies made from aarying gluten-free flour combinations - Lim, Ellise Nicolle B.; Basinag, Airisse Rae P. (Quezon City University of the Philippines Diliman, 2024)
The demand and popularity for gluten-free products, driven by the increasing prevalence of conditions like celiac disease and gluten intolerance, pose a significant challenge in achieving acceptable quality of gluten-free products due to substituting gluten in their production and development. Hence, the study aimed to assess the quality of gluten-free brownies made from a combination of various locally produced gluten-free flour combinations, namely coconut and arrowroot flour (GF1), arrowroot and brown rice flour (GF2), and brown rice and coconut flour (GF3), and their effects on the physical and chemical properties and sensory characteristics of the gluten-free brownies. Results showed that gluten-free brownies had significantly higher crude fiber levels (p<0.05) than the control, with GF2 having the highest crude fiber content. Hardness or depth of penetration value of the GF2 brownies also exhibited a significantly greater (p<0.05) depth than wheat brownies, indicating a softer consistency. The sensory evaluation showed that GF2 had the highest overall acceptability among the gluten-free brownie formulations, interpreted as ‘like moderately’ on the 9-point hedonic scale. Moreover, correlation analysis revealed that hardness and all sensory attributes exhibited strong positive correlations with overall acceptability, with mouthfeel demonstrating the highest correlation value. Despite this, their sensory attributes did not exhibit significant differences (p>0.05). Therefore, these gluten-free flour combinations are excellent alternatives or substitutes for wheat flour to produce gluten-free food products.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Celiac disease; Brownies;.; Gluten-free products; Gluten-free flour; Gluten intolerance